Effect of interstage air-cooling on reducing power consumption of fuel cell two-stage centrifugal pressurization system - Hanqian Yang; Tianyou Li; Rongji Wang; Suifeng Cao; Liaoping Hu; Jianqin Fu (Case Studies in Thermal Engineering)
As a critical component in fuel cell air supply systems, air compressors account for approximately 20 % of the total power consumption in fuel cell systems, significantly limiting overall efficiency improvement. This study proposes a novel enhanced interstage air-cooling method for two-stage centrifugal supercharging systems applied in fuel cells. Two compact interstage air-cooling configurations were designed, and corresponding full-domain Computational Fluid Dynamics (CFD) simulation models of the two-stage supercharging system were established to analyze the aerodynamic performance enhancement through interstage air-cooling. The research results show: (1) The interstage air-cooling expands the surge margin of the two-stage supercharging system, and broadens the high-efficiency operating range (isentropic efficiency ≥70 %) by 77.8 % and 74.6 % respectively. (2) At design conditions, the two interstage air-cooling schemes respectively reduce the average temperature at the high-pressure stage outlet section by 6.1 K and 8.0 K, correspondingly decrease system power consumption by 2.04 % and 2.25 %, and improve efficiency by 1.64 % and 1.61 % respectively; (3) Under near-surge operating conditions, the two-stage centrifugal pressurization system exhibits performance improvement. This study provides theoretical analysis basis for performance optimization of two-stage centrifugal pressurization systems and offers reference for product design.